Alienation from Study as a Predictor of Burnout in University Students: the Role of the Educational Environment Characteristics - Osin E.N (Moscow State University of Psychology and Education, 2015)
The paper presents two studies aimed at development and validation of a scale of alienation in educational context. The first study using samples of university students (N = 395) and high school students (N = 194) involves structural validation of Subjective Alienation Questionnaire for Students using confirmatory factor analysis. The scales of the questionnaire have shown acceptable internal consistency (α = 0,70-0,92) and predictable associations with measures of subjective and psychological well-being, locus of control, life meaning, generalized self-efficacy, and hardiness. The second study using a sample of university students (N = 152) focused on the associations of alienation, burnout, and academic motivation with learning environment characteristics, well-being, and self-reported academic achievement. According to the resulting model, learning motivation and alienation reflect characteristics of relation of the student to the object of learning, whereas burnout reflects the resulting characteristics of learning process. Burnout was predicted by excessive difficulty of learning tasks, high workload, and alienation. Alienation was predicted by low teacher support, low clarity of learning requirements, and lack of choice in studies. Alienation and burnout mediated the asso-ciations of these learning environment characteristics with self-reported academic success and subjective well-being of students.